Nassib Sharif Mortada between Clarity and Ambiguity - Hussein Oleiwi, Najlaa Abdul; Mahmod Khatab, Shaker (Opción, 2019)
The relative is an old poetic art renewed, with images, ideas and meanings of various meanings in one particular is to describe the beauties of women and charms, and how the poet begins the beginning of his poem through a coherent editorial fresh words have very influential meanings, as it attracts the attention of the recipient and makes him eager and eager to realize the extent The poet’s creativity in depicting his beloved or describing the effects of their homes and the change that took place in expressive language and understandable, and as shown that Sharif Murtada of poets who combined in their relative between long weights and short weights, his tendency to sober weights came a tradition and keep up with those who preceded him For poets, his tendency to short weights came to keep pace with the develop- ments of the times and innovations and changes in it, as well as the mixing of Arabs with other cultures that have entered Islam, and the phenomenon of relativism is a phenomenon that has been transformed or changed, as it has shifted from the description of beauty and riding on it to describe The ships, and the description of the desert to describe the beautiful and picturesque nature, as well as that the relative of the poet has been free from among the things that prevailed in that era of singing and his instruments and descrip- tions because they are contrary to the chastity and dignity of the poet.